Penerapan Quantum GIS dalam Pengembangan 3D Maps pada Aplikasi Bakunjangan Pariwisata - Hidayat, Muhammad; Rizki Zulkarnain, Muhammad (Jurnal Teknologi Informasi dan Pendidikan, 2024)
This research explores the use of Quantum GIS (QGIS) in developing 3D maps for the Bakunjangan tourism application in Banjarmasin City. The integration of spatial data, sensors, and open data sources such as OpenStreetMap (OSM) aims to improve accuracy, consistency, and visitor experience. The development of 3D maps follows the System Development Life Cycle (SDLC) method, which outlines strategies and processes for developing, designing, and maintaining software projects, ensuring that all goals, objectives, functionalities, and user needs are met. The urgency of this research lies in its ability to support the Banjarmasin City government in managing and developing local tourism, especially with the increase in tourist visits from 2,487 in 2022 to 3,895 in 2023. The 3D map feature in the Bakunjangan Application is expected to provide accurate information and a more satisfying experience for tourists, as well as enhance the competitiveness of tourism at the national level. The development of the 3D maps was conducted after a survey of 55 Ground Control Points (GCP) in various tourist areas. The QGIS application, with the help of the Qgis2threejs plugin, facilitates the creation of 3D map animations, although five tourist attractions could not be animated. To optimally display the 3D maps, an internet connection with a minimum speed of 10 Mbps is required. As a result, the Bakunjangan Application produced 65 interactive user interfaces and 50 3D animations of tourist attractions, with an application feasibility rating of 89%, placing it in the excellent category.